The Supreme Court and Islamic Family Law Reform: A Review of Policy Direction and Implementation Challenges - Muchlis; Ramdani Wahyu Sururie; Idzam Fautanu; Usep Saepulah; Gugun Gumilar (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2025)
The reform of Islamic family law is not only related to legal matters but also to the social and cultural values surrounding it. In Indonesia, the development of Islamic family law has relied on the government and the legislature, as reflected in the enactment of the Marriage Law and the Compilation of Islamic Law. However, the lengthy legislative process, which is often laden with political interests, makes it difficult to accelerate legal reform. This study aims to analyze the role of the Supreme Court, particularly the Religious Chamber, as an institution with the potential to expedite the reform of Islamic family law through its judicial authority. applying a qualitative method and descriptive analysis, this research finds that the Supreme Court contributes significantly to Islamic family law reform through progressive decisions and the Plenary Meetings of the Religious Chamber producing legal formulations. The main findings show that the reform agenda promoted by the Supreme Court focuses on strengthening the protection of women’s and children’s rights. The study also identifies two major challenges in implementation: variations in judges’ adherence to the plenary formulations and limited public access to information regarding the plenary outcomes. These findings underscore the importance of optimizing the role of the Supreme Court as a strategic driver in accelerating the reform of Islamic family law in Indonesia.